WELDING FUMES HEALTH INDEX AS ASSESSMENT TOOL FOR Automotive Component Manufacturing Industries - Azlan Hariri; Abdul Mutalib Leman; Mohammad Zainal Md Yusof; Nuur Azreen Paiman; Yahaya Ramli (Penerbit UTHM, 2020)
The book was written based on our study to look at the possibility of developing an index as a risk assessment tool in the industry. During execution of this study, we discover interesting theory and approach in developing a satisfying index, which was very limited explained in books and journal articles. Thus, this book is written to share our research done on this subject. This book covers the theory behind index development and the practice example on how we collected data of 127 industrial welders and successfully transform those data to become an index for risk assessment tool in industry. This book was written to share the knowledge we gain with research students, policy-maker, agency or stakeholders that had been searching for an example of how an index was being developed. We belief that a better understanding on the topics will generate more research done on index development in the future by considering all the aspects that need to be fulfilled to develop a good index.